Pendampingan Industri Pengolahan Telur Asin di Desa Pendem Kecamatan Junrejo Kota Batu - Praharjo, Ardik; Robbie, R. Iqbal (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Society in general requires an activity to increase income and productivity. The importance of cooperation between citizens in realizing these desires must be in line and supported by the Village Government, so that the development planning process can run optimally. The desire of residents who are accommodated by the Village Government generates ideas to form a Tourism Village that is packaged in the theme "Halal Traveling Pendem Village". In order to support the establishment of the Tourism Village, the Village Government invited the stakeholders to include the academic community of the University of Muhammadiyah Malang in particular the Management Study Program of the Faculty of Economics and Business to formulate the master plan. The initial phase of the Village Government increases the awareness of its citizens to equal perception by evaluating themselves and seeing their weaknesses, one of which is the formation of small businesses through independent groups or Bumdes to strengthen the community's economy. In addition, it will foster small groups from each hamlet who have an effort to be professional both in terms of ability, awareness, and desire to form the Tourism Village. During this time the activities carried out are still limited to fill leisure and channel hobbies and as a side business do not have the idea to be used as a business opportunity. So there needs to be a change in mindset from just channeling a hobby into a mindset of entrepreneurs.